Silvicultural disturbance severity and plant communities of the southern Canadian boreal forest - Haeussler, Sybille; Bedford, Lorne; Leduc, Alain; Bergeron, Yves; Kranabetter, J. (Silva Fennica, 2002)
Boreal forest ecosystems are adapted to periodic disturbance, but there is widespread concern that conventional forest practises degrade plant communities. We examined vegetation diversity and composition after clearcut logging, mechanical and chemical site preparation in eight 5- to 12-yr old studies located in southern boreal forests of British Columbia and Quebec, Canada to find useful indicators for monitoring ecosystem integrity and to provide recommendations for the development and testing of new silvicultural approaches. Community-wide and species-specific responses were measured across gradients of disturbance severity and the results were explained in terms of the intermediate disturbance hypothesis and a simple regeneration model based on plant life history strategies. Species richness was 30 to 35% higher 5 to 8 years after clearcut logging than in old forest. Total and vascular species diversity generally peaked on moderately severe site treatments, while non-vascular diversity declined with increasing disturbance severity. On more-or-less mesic sites, there was little evidence of diversity loss within the range of conventional silvicultural disturbances; however, there were important changes in plant community composition. Removing soil organic layers caused a shift from residual and resprouting understory species to ruderal species regenerating from seeds and spores. Severe treatments dramatically increased non-native species invasion. Two important challenges for the proposed natural dynamics-based silviculture will be 1) to find ways of maintaining populations of sensitive non-vascular species and forest mycoheterotrophs, and 2) to create regeneration niches for disturbance-dependent indigenous plants without accelerating non-native species invasion.